Numerical solutions of mixed convection flow on a solid sphere embedded in a porous medium filled by a nanofluid containing gyrotactic microorganisms - Leony Tham; Roslinda Nazar; Ioan Pop (2012)
In this paper, the steady mixed convection boundary layer flow over a solid sphere with a constant surface temperature embedded in a porous medium saturated by a nanofluid containing both nanoparticles and gyrotactic microorganisms in a stream flowing vertically upwards for both cases of a heated and cooled sphere, is numerically studied. The resulting system of nonlinear partial differential equations is solved numerically using an implicit finite-difference scheme. By considering the governing parameters, namely the mixed convection parameter λ, the bioconvection Lewis number Lb, the traditional Lewis number Le, the bioconvection Péclet number Pb, the buoyancy ratio Nr, the bioconvection Rayleigh number Rb, the Brownian motion Nb and the thermophoresis Nt, the numerical results are obtained and discussed for the local density number of the motile microorganisms as well as the velocity, temperature, nanoparticle volume fraction and density motile microorganisms profiles.